Transforming the non-military structures of global governance: Assessing priorities for chapter 5 of the Pact for the Future - Harris Gleckman (South Centre, 2024)
The complex web of challenges confronting humanity - climate change, pandemics, economic inequality, and violent conflict - demands a robust global governance system. However, the current architecture, centred on the United Nations, is widely considered inadequate. This document delves into this debate, analysing proposed reforms for the UN system in the Summit of the Future context. At the centre of the discussion is the need for an update to the UN System, particularly strengthening its effectiveness, efficiency, and democratic representation. The document recognises the need for prioritisation, focusing on reforms that tackle the "triple crisis" - climate change, inequality, and conflict - while remaining politically achievable. The document also highlights the disconnect between economic and political institutions, arguing for a more unified approach. Reform proposals encompass a wide spectrum, including institutional changes, consultative practices, decision-making rules and financing. The reforms proposed aim to empower the UN to take decisive action on pressing global issues, looking at past reform efforts, assessing the feasibility of current proposals, and prioritising those most likely to yield tangible results. This publication aims to serve as a roadmap for navigating the complexities of UN reform and providing a comprehensive overview of proposed changes towards shaping a more effective and democratic global governance system for the future.
Keywords: 300; Basel Institutions; Bretton Woods Institutions (BWIs); Civil Society (CSOs); Climate Change; Environmental Crisis; Global Governance; Human Rights; Multilateralism; Multistakeholderism; Pact for the Future; Reform of the International Financial System; Summit of the Future; UN 2.0.; UN Charter; UN Reform; United Nations (UN); United Nations System; World Trade Organization (WTO)